Stakeholders pressures on corporate social responsibility issues: combining theories of Mitchell and Simons (Costos y Gestión, 2022)
The main purpose of this work is to investigate organizations behavior facing pressure from stakeholders in Corporate Social Responsibility (CSR) issues. Two objectives are presented: (1) to identify stakeholders pressures on organizations and (2) to analyze what type of response organizations give from their control systems and if they depending on the group of stakeholders and the type of pressure.We find this study important because of what was published so far almost exclusively refer to the concerns of stakeholders on environmental issues, leaving out other issues related to CSR. That is why we intend to analyze other CSR issues and not exclusively environmentals. Furthermore, it is of our interest to discover accounting as a scientific discipline capable of covering an ever-widening spectrum of topics.The leading question is: are management control systems capable of take place identifying stakeholders pressures and their degree of relevance to their correct management? To hypothesize an answer, we start from the following theoretical framework, which we will analyze and combine in the development of this presentation:• CSR as a general framework,• the stakeholder theory proposed by Mitchell in 1997, which identifies and classifies stakeholders pressures in an organization,• levers of control theory developed by Simons (1994, 1995), to identify managers’ responses to stakeholder pressures, analyzing the different uses of management control systems.This work is presented as an essay and a literatura review in the aformentioned theories to adress the possibilities they offer to answer the leading question
Keywords: stakeholders; pressures; management control systems